Anomalous Work Hardening Behavior of a Single Crystalline Co-Base Superalloy - Bezold, Andreas; Volz, Nicklas; Xue, Fei; Neumeier, Steffen; Göken, Mathias (Alloys, 2022)
The defect evolution associated with an anomalous work hardening behavior of a single crystalline quaternary Co-Al-W-Ta superalloy at 950 °C was investigated by transmission electron microscopy. As plastic deformation is initially confined to the γ matrix channels, a plateau arises in the stress-strain curve after yielding. At about 1% plastic strain, extensive shearing of the γ′ precipitates under superlattice stacking fault formation occurs leading to extreme work hardening rates up to 12 GPa and a total increase in stress of about 200 MPa. Additional investigations on the temperature and strain-rate dependence of the anomalous work hardening behavior reveal the significance of diffusion and segregation processes on the stress-strain curve and the work hardening behavior.
Keywords: superalloy; yielding behavior; work hardening; transmission electron microscopy (TEM); high-temperature deformation

Design of a Co–Al–W–Ta Alloy Series with Varying γ′ Volume Fraction and Their Thermophysical Properties - Volz, Nicklas; Xue, Fei; Bezold, Andreas; Zenk, Carolin; Fries, Suzana G.; Schreuer, Juergen; Neumeier, Steffen; Göken, Mathias (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2021)
The γ′ volume fraction is a key parameter in precipitation-strengthened Co- and Ni-base superalloys and mainly determines the alloys’ properties. However, systematic studies with varying γ′ volume fractions are rare and the influence on thermal expansion has not been studied in detail. Therefore, a series of six Ta-containing Co-based alloys was designed with compositions on a γ–γ′ tie-line, where the γ′ volume fraction changes systematically. During solidification, Laves (C14-type) and µ (D85-type) phases formed in alloys with high levels of W and Ta. Single-phase γ or two-phase γ/γ′ microstructures were obtained in four experimental alloys after heat treatment as designed, whereas secondary precipitates, such as χ (D019-type), Laves, and μ, existed in alloys containing high levels of γ′-forming elements. However, long-term heat treatments for 1000 hours revealed the formation of the χ phase also in the former χ-free alloys. The investigation of the thermal expansion behavior revealed a significant anomaly related to the dissolution of γ′, which can be used to determine the γ′ solvus temperature with high accuracy. Compared to thermodynamic calculations, differential scanning calorimetry (DSC) and thermal expansion analysis revealed a larger increase of the γ′ solvus temperatures and a lesser decline of the solidus temperatures when the alloy composition approached the composition of the pure γ′ phase.

Double minimum creep in the rafting regime of a single-crystal Co-base superalloy - Xue, Fei; Zenk, Christopher; Freund, Lisa; Hoelzel, M.; Neumeier, Steffen; Göken, Mathias (Scripta Materialia, 2018)
To investigate whether the formation of rafts in Co-base superalloys has a hardening or softening effect, the single crystal deformation behavior was studied in the high temperature/low stress creep regime. The large positive lattice misfit of the investigated Co-base superalloy led to a pronounced directional coarsening of the microstructure normal to the stress axis during compressive creep at 950 degrees C/150 MPa. Two creep minima were observed similar to Ni-base superalloys under tensile creep. Rafting was accompanied by a decreasing creep rate indicating a hardening effect, although cutting of gamma' rafts by partial dislocations under the formation of stacking faults occurred. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Co-base superalloys; Lattice misfit; Directional coarsening; Creep; Neutron diffraction

Influence of the γ′ Volume Fraction on the High-Temperature Strength of Single Crystalline Co–Al–W–Ta Superalloys - Xue, Fei; Bezold, Andreas; Volz, Nicklas; Kirchmayer, Andreas; Zenk, Christopher; Neumeier, Steffen; Göken, Mathias (Crystals, 2023)
Understanding the influence of γ′ and secondary-phase fractions on the mechanical properties of superalloys is very important to optimize these high-strength materials. So far, this has not been systematically investigated for the novel class of Co-based superalloys. In this study, a Co–Al–W–Ta model alloy series was designed with compositions of γ/γ′ on the tie-line and an increasing γ′ volume fraction of up to 70% after heat treatment at 900 °C, while a few alloys are unexpectedly out of γ/γ′ two-phase region with an additional secondary phase fraction of up to 15%. The high-temperature strength and creep properties were evaluated by compression tests up to 1050 °C and compressive creep experiments at 950 °C, respectively. At temperatures of up to 1050 °C, an increasing γ′ volume fraction consistently increased the yield strength, which was not dramatically changed by the presence of secondary phases. Significant work hardening was found in alloys with γ′ volume fractions of 65–70% during compression testing, but not in alloys with either a lower γ′ volume fraction (<50%) or a high fraction of secondary phases ( 15%). Similar to the yield strength, the creep strength also increased continuously with the γ′ volume fraction, but was greatly reduced with an increasing fraction of secondary phases. The best creep performance at 950 °C and 200 MPa was found in the alloy with the highest γ′ volume fraction and no secondary phases. At higher creep stresses, rafting contributed significantly to the hardening and, again, the alloy with a high γ′ volume fraction and a small amount of secondary phases exhibited the highest strength.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Co-based superalloys; compression test; creep; rafting; stacking faults; transmission electron microscopy

Understanding creep of a single-crystalline Co-Al-W-Ta superalloy by studying the deformation mechanism, segregation tendency and stacking fault energy - Volz, Nicklas; Xue, Fei; Zenk, Christopher; Bezold, Andreas; Gabel, Stefan; Subramanyam, A. P.A.; Drautz, R.; Hammerschmidt, T.; Makineni, S. K.; Gault, B.; Göken, Mathias; Neumeier, Steffen (Acta Materialia, 2021)
A systematic study of the compression creep properties of a single-crystalline Co-base superalloy (Co-9Al-7.5W-2Ta) was conducted at 950, 975 and 1000°C to reveal the influence of temperature and the resulting diffusion velocity of solutes like Al, W and Ta on the deformation mechanisms. Two creep rate minima are observed at all temperatures indicating that the deformation mechanisms causing these minima are quite similar. Atom-probe tomography analysis reveals elemental segregation to stacking faults, which had formed in the γ′ phase during creep. Density-functional-theory calculations indicate segregation of W and Ta to the stacking fault and an associated considerable reduction of the stacking fault energy. Since solutes diffuse faster at a higher temperature, segregation can take place more quickly. This results in a significantly faster softening of the alloy, since cutting of the γ′ precipitate phase by partial dislocations is facilitated through segregation already during the early stages of creep. This is confirmed by transmission electron microscopy analysis. Therefore, not only the smaller precipitate fraction at higher temperatures is responsible for the worse creep properties, but also faster diffusion-assisted shearing of the γ′ phase by partial dislocations. The understanding of these mechanisms will help in future alloy development by offering new design criteria.<br
Keywords: Co-base superalloys; Directional coarsening; Creep; Stacking fault energy; DFT

Understanding raft formation and precipitate shearing during double minimum creep in a γ′-strengthened single crystalline Co-base superalloy - Xue, Fei; Zenk, Christopher; Freund, Lisa; Neumeier, Steffen; Göken, Mathias (Philosophical Magazine, 2020)
The compressive creep deformation behavior of a Co-base single-crystalline superalloy is studied in the high temperature / low stress regime at 950°C/150 MPa. Emphasis is placed on the mechanisms causing the double minimum creep behavior consisting of a local and a global creep rate minimum. The local minimum occurs at ∼0.2% strain with dislocation accumulation at γ/γ′ interfaces after bowing out of dislocations in horizontal matrix channels. Plate-like rafting occurring normal to the applied stress axis in the early creep stages is regarded as the primary reason for the decreasing creep rate until the global minimum takes place at ∼0.8% strain. In the final creep stage following the global minimum the creep rate accelerates due to coarsening and extensive precipitate shearing. The shearing by partial dislocations leads to the formation of numerous stacking faults, nano/microtwins, and occasionally to the formation of small amounts of ordered D019-Co3W precipitates. The reasons for twinning and second phase formation as well as differences of the deformation mechanisms between Co- and Ni-base superalloys during double minimum creep are discussed in detail in this work.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Co-base superalloys; creep; deformation; directional coarsening; transmission electron microscopy